2007
DOI: 10.21273/horttech.17.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Naphthaleneacetic Acid, Ethephon, and Gibberellin A4 + A7 Have Variable Effects on Flesh Firmness and Return Bloom of Apple

Abstract: Experiments were conducted in commercial apple (Malus ×domestica) orchards in the southeastern U.S. between 1998 and 2006 with the primary objective of evaluating the effects of naphthaleneacetic acid (NAA) and ethephon on return bloom. NAA increased return bloom in six of 10 experiments, whereas ethephon increased return bloom in four of seven experiments. Four biweekly applications of 5 ppm NAA during June and July (early summer NAA) increased ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Many researchers suggested that ethephon promotes generative growth (Greene, 1996;Westwood, 1995), whereas there are insignificant findings (McArtney et al, 2007;Schmidt et al, 2009). Ethephon was also found as insignificant in the first three years of our trial.…”
Section: Ethephon Trialmentioning
confidence: 48%
See 2 more Smart Citations
“…Many researchers suggested that ethephon promotes generative growth (Greene, 1996;Westwood, 1995), whereas there are insignificant findings (McArtney et al, 2007;Schmidt et al, 2009). Ethephon was also found as insignificant in the first three years of our trial.…”
Section: Ethephon Trialmentioning
confidence: 48%
“…High doses (above 500 ppm) were not recommended for bearing trees due to increasing thinning, fruit drop, and ripening (Byers, 1993). Bukovac et al (2006) and McArtney et al (2007) recommended 200 ppm of ethephon to enhance return bloom. However, in our study, ethephon became inefficient, and we think that a trial with higher doses could be more effective in our environment.…”
Section: Ethephon Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Several PBR compounds, including paclobutrazol (El Hodairi and Canham, 1990), daminozide (Jones et al, 1989), triodobenzoic acid (Bukovac, 1968), NAA (Harley et al, 1958), and ethephon (ETH) (Williams, 1972) have enhanced flowering in apple trees the year following application. Several studies report enhanced flowering in bearing apple trees from foliar applications of ETH at concentrations ranging from 150 to 1000 mg•L -1 , with treatments varying by number of applications, application dates, and cultivars (Bukovac et al, 2006;McArtney et al, 2007;McArtney et al, 2013;Schmidt et al, 2009;Williams, F o r R e v i e w O n l y 1972). Similar results have been obtained with NAA at concentrations of 4 to 5 mg•L -1 , also with varying numbers of applications and application dates (McArtney et al, 2007;McArtney et al, 2013).…”
mentioning
confidence: 99%
“…Several studies report enhanced flowering in bearing apple trees from foliar applications of ETH at concentrations ranging from 150 to 1000 mg•L -1 , with treatments varying by number of applications, application dates, and cultivars (Bukovac et al, 2006;McArtney et al, 2007;McArtney et al, 2013;Schmidt et al, 2009;Williams, F o r R e v i e w O n l y 1972). Similar results have been obtained with NAA at concentrations of 4 to 5 mg•L -1 , also with varying numbers of applications and application dates (McArtney et al, 2007;McArtney et al, 2013). Spray programs of ETH or NAA are recommended to enhance flowering in bearing and non-bearing apple trees in tree fruit production guides (e.g.…”
mentioning
confidence: 99%